Diseño y construcción de un calentador solar de placa plana combinado con un sistema de calefacción convencional a gas utilizando la discreción de temperaturas para el laboratorio de energías alternativas del AEIRNNR de la UNL. - Carrión Borja, Andrés Antonio (2010)
The present thesis project understands: “I Design and Construction of a Solar Heater of badge plane cocktail with a system of conventional heating to gas using the discretion of temperatures for the laboratory of Alternative Energy of the Area of Energy, the Industries and the Nonrenewable Natural Resources of U.N.L.” Having as specific objectives: to Determine the appropriate system and insurance for the solar process of heating of water coupled to a system to gas, to design a solar collector for heating of water coupled to a heating system of to gas, to build a system combined for heating of water sun-gas with an appropriate and efficient operation that allows to make practical in the students of Electromechanical Engineering and in turn to implement a data acquisition system for monitorial the operation of the team. It is necessary to emphasize the importance of this project, since their construction guaranteed a conservation of the atmosphere and a significant saving in the electric power use, or GLP for processes of Heating of water for human consumption. In the course of the investigative process, it was determined convenient to add a device of control of temperature for the water, that which guaranteed a pleasant temperature for their use and consumption.